Assessment of University of Wisconsin - La Crosse undergraduate students' attitudes toward gay men and lesbians - Nichols, Angela C. (My University, 1998)
This survey assessment provided a baseline study about attitudes UW-L undergraduates have toward gay men and lesbians, and consisted of five parts eliciting both qualitative and quantitative data. Hypotheses were tested for a comparison of group means for independent samples, using ttests and analysis of variances (ANOVAs). A content analysis created in 1987 by Gregory Herek was built upon in this study by founding a new category of influence on attitudes toward gay men and lesbians. This new category is known as the "Indirect Experiential-Schematic" psychological function. The sample for this study (n = 1,180) reflected 15% of the undergraduate student population at UW-L. Results indicate that contact with gay, lesbian, and bisexual people, students' major field of study, age, gender, race/ethnicity, residency (on or off campus living), class (freshman, sophomore, junior, senior), exposure to material about homosexuality, and knowledge of GLB harassment or physical assault at UW-L are all influential variables affecting these undergraduate students' attitudes toward gay men and lesbians. Three themes from interviews emerged illustrating the sharply contrasting differences in the daily lives of GLB students in comparison to heterosexual students. They were, (1) individuals who are gay, lesbian, or bisexual have a unique array of stressors with which they must deal, namely fear, (2) they are less involved on campus, which leaves them more isolated and alone and, (3) they are less likely than heterosexual students to seek professional help for their stressors. The opposite appears to be true for heterosexual students.
Keywords: University of Wisconsin - La Crosse -- Students -- Attitudes; Gay men -- Wisconsin -- La Crosse -- Public opinion; Lesbians -- Wisconsin -- La Crosse -- Public opinion